A conversation analytic approach to the interactional impact of repair strategies in mediated settings - ÖZSÖZ, BURAK (My University, 2021)
First introduced by Schegloff, Jefferson and Sacks (1977), 'repair' as a discourse practice is one of the key structural features of talk in interaction. By definition, repair is a process in which conversational problems that occur on various levels of linguistic structure are fixed. Trouble sources the participants choose to repair in speech generally include errors in grammar, word choice and supra-segmental features, such as pronunciation. Once the trouble source is located by one of the primary participants, repair is either initiated by the current speaker or the other parties involved. The structure and the organisation of social interaction in monolingual settings, whether institutional or not, have been explored in numerous studies via a series of concepts, including turn-taking, sequences, adjacency pairs and repairs among others. However, the studies where such key concepts have been applied to the field of interpreting are rather few. This study seeks to investigate various sequences of interpreter mediated encounters where possible breakdowns occur in the renditions of the interpreters mediating the talk. The interactional impact of certain troubles in interpreter mediated interactions and how interpreters deal with them to restore the flow of talk will also be explored.

Schegloff, Jefferson ve Sacks (1977) tarafından literatüre kazandırılan ‘onarım’ sözlü dilin yapısal özelliklerinden biridir. Temel bir tanımla onarım, farklı düzeydeki dil yapılanmalarında ortaya çıkan konuşmaya dair sorunların çözüme kavuşturulduğu bir süreçtir. Katılımcıların konuşma esnasında onarma eğilimi gösterdiği sorunlar dilbilgisel hatalar, kelime seçimi ve sesletim gibi parça-üstü yapıları içerir. Sorunun kaynağının belirlenmesi ile birlikte onarım süreci konuşmacanın kendisi veya bir başka katılımcı tarafından başlatılır. Söz sırası alma, sıra dizisi, ardışık çiftler ve onarım gibi toplumsal etkileşimin örgütlü yapısal özellikleri tek dilli kurumsal ve gündelik iletişim ortamlarında olmak üzere birçok çalışmada ele alınmış olmasına karşın, bu kavramsal gereçlerin sözlü çeviri ortamında araştırıldığı çalışmalar sayıca oldukça azdır. Bu çalışmada, çevirmenin sözlü çeviri ediminde meydana gelebilecek olası sorunların belli sıra dizileri dâhilinde çevirmen tarafından nasıl ele alındığı ve düzeltildiği ve bu eylemlerin etkileşimsel sonuçlarının neler olabileceği araştırılmaktadır.
Sözlü çeviride onarım stratejilerinin etkileşimsel değerine konuşma çözümlemesi odaklı yaklaşım
Keywords: Konuşma çözümlemesi; onarım; sözlü çeviri ortamı; Conversation analysis; repair; mediated talk